QuantiFERON-TB Gold Plus Assay in Patients With Latent vs. Active Tuberculosis in a Low Incidence Setting: Level of IFN-γ, CD4/CD8 Responses, and Release of IL-2, IP-10, and MIG - Carrère-Kremer, Séverine; Kolia-Diafouka, Pratt; Pisoni, Amandine; Bolloré, Karine; Peries, Marianne; Godreuil, Sylvain; Bourdin, Arnaud; Van de Perre, Philippe; Tuaillon, Edouard (Frontiers in Microbiology, 2022)
Objectives. We analyzed results of the QuantiFERON Glod Plus assay (QFT) and cytokine patterns associated with Active tuberculosis (ATB) among patients with positive QFT. Methods. Hundred-ninety-five patients QFT-positive, 24 had an ATB and 171 a LTBI. IFN-γ secretion was analyzed relatively to IL-2, IP-10 and MIG secretion, and compared between two sets of peptide antigens (tube 1 - CD4+ T cell stimulation; tube 2 - CD4+/CD8+ T cell response). Results. Higher IFN-γ response were measured in the ATB group (p=0.0089). There was a lower ratio of tube 1/tube 2 IFN-γ concentrations in the ATB group (p = 0.0009), and a median (IQR) difference between the two sets of -0.82 IU/ml (-1.67 to 0.18) vs -0.07 IU/ml (-0.035 to 0.11, p<0.0001), in the ATB group compared to the LTBI group, respectively. In addition, patients with low ratios of IL-2/IFN-γ, IP-10/ IFN-γ, and MIG/IFN-γ were much more likely to have ATB. Conclusion. High level of IFN-γ secretion, preferential IFN-γ response in tube 2, and impaired capacity of IL-2, IP-10, and MIG release relatively to IFN-γ secretion were associated with ATB. These features of T cell response may be helpful in low prevalence settings to suspect ATB in patients tested positive for IGRA.